Sex differences in asthma: omics evidence and future directions - Peng, Bichen; Ye, Weiyi; Liu, Shuai; Jiang, Yue; Meng, Ziang; Guo, Miao; Zhi, Lili; Chang, Xiao; Shao, Lei (Frontiers in Genetics, 2025)
Asthma is a common and complex heterogeneous disease, with prevalence and severity varying across different age groups and sexes. Over the past few decades, with the development of high-throughput technologies, various “omics” analyses have emerged and been applied to asthma research, providing us with significant opportunities to study the genetic mechanisms underlying asthma. However, despite these advancements, the differences and specificities in the genetic mechanisms of asthma between sexes remain to be fully explored. Moreover, clinical guidelines have yet to incorporate or recommend sex-specific asthma management based on high-quality omics evidence. In this article, we review recent omics-level findings on sex differ-ences in asthma and discuss how to better integrate these multidimensional findings to generate further insights and advance the precision and effectiveness of asthma treatment.